Paranoid Schizophrenia with Risk Factors of Disharmonious Family Relationships - Dasa Novita, Khuznita; Alhabsy, Muzna (Family Medicine Department, Faculty of Medicine, Brawijaya University, 2024)
Schizophrenia is a chronic mental disorder characterized by episodes of psychosis, including hallucinations, delusions, and disorganized thinking with longterm of antipsychotic medications that can significant effect complication such as the development of extrapyramidal syndrome (EPS). This case aims to explore the interplay between the neurological side effects of antipsychotic medications, specifically EPS, and the impact of family dynamics on the course of schizophrenia. Understanding this relationship is essential for developing comprehensive treatment plans that address both the medical and psychosocial needs of patients with schizophrenia, thereby improving their quality of life.